2014
DOI: 10.1016/j.redox.2014.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal vitamin C deficiency results in differential levels of oxidative stress during late gestation in foetal guinea pig brains

Abstract: Antioxidant defences are comparatively low during foetal development making the brain particularly susceptible to oxidative stress during antioxidant deficiencies. The brain is one of the organs containing the highest concentration of vitamin C (VitC) and VitC deficiency during foetal development may place the brain at risk of redox status imbalance. In the present study, we investigated the developmental pattern and effect of VitC deficiency on antioxidants, vitamin E and superoxide dismutase (SOD), assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…The emergence and spread of excitation, muscle contraction, oxygen transport, blood properties, immune protection, the transmission of hereditary information, etc., is associated with proteins. In addition, proteins are a source of energy (Oltjen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The emergence and spread of excitation, muscle contraction, oxygen transport, blood properties, immune protection, the transmission of hereditary information, etc., is associated with proteins. In addition, proteins are a source of energy (Oltjen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the large amount of work on the subject, there is a need for additional experimental data to expand our knowledge about the mechanisms of action of antioxidants, especially products of natural origin. Therefore, the search for new drugs for stress correction, as well as the comprehensive use of antioxidants and products of natural origin as stress correctors, has of great practical importance (Mizutani & Masaki, 2014;Paidi et al, 2014;Ahn, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Adult guinea pigs (Charles River laboratories, Kiessleg, Germany) were sacrificed according to previously described procedures [23]. In short, dams were pre-anesthetized with butorphanol (10mg/ml, Torbugesic Vet, Orion Pharma Animal Health, Nivå, Denmark) and placed on isoflurane inhalation anaesthesia (Isoba Vet, Intervet…”
Section: Brain Tissuementioning
confidence: 99%
“…Foetuses were delivered by caesarean section as previously described [23]. Immediately following delivery, pups were decapitated and the brain excised and subsequently Kinetex C 18 column (Phenomenex) showed the most promising chromatograms.…”
Section: Primary Neuronal Cell Culturementioning
confidence: 99%
“…Intrauterine growth retardation was related to insufficient vitC status in guinea pigs [10]. More recently, experimental reports from animal studies demonstrated that CNS development in particular requires high amounts of vitC and may be impaired by an inadequate maternal supply [12,13,14,15]. …”
Section: Introductionmentioning
confidence: 99%